THE DEVELOPING OF BUSY BOOK MEDIA FOR LEARNING PROCESS: IMPLEMENTING STUDY IN PRIMARY SCHOOL - Helminsyah, Helminsyah; Kasmini, Lili; Mardhatillah, Mardhatillah; Musdiani, Musdiani; Marlini, Cut; Subhananto, Aprian; Fuad, Zaki Al (Teunuleh Publisher, 2022)
Interviews with SD Negeri 16 Banda Aceh class teachers revealed that the learning media used in grade I primary schools were less varied, less interesting, and the use of busy book media had never been used for students' speaking skills, with the development of busy book media expected to produce instructional media that were interesting and fun as well as being a solution for various problems in the learning process. Based on this case, the Busy Book media can be said to be valid used in the learning process ss in the first grade of elementary school. This has led researchers to conduct research under the title